PENGARUH KUALITAS PELAYANAN KINERJA PEGAWAI ADMINISTRASI AKADEMIK TERHADAP KEPUASAN MAHASISWA FAKULTAS EKONOMIKA DAN BISNIS UNIVERSITAS DIPONEGORO - Arimawati, Renata; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2013)
The growing pattern of education is so fast and turns that led to competiton in the field of education, especially at college. The research was conducted at the Faculty of Economics and Business Diponegoro University Semarang. This study aims to determine the effect of service Quality Variables. Tangible/ Physical evidence, Reliability/Durability, Responsiveness, Assurance, Empathy towards Studentâ€™s satisfaction part of Economics anf Business Diponegoro University. In this study data were collected by using questionnaire to 98 respondents. Which aim to determine the response of the respondents to each variable. The test data which is used include validity test, reliability test, classic assumptionÂ test (multicollinearity, normality, heteroscedasticity), multiple linear regression, goodness of fit ( F test, t test, the coeficient of determination). From the result that using the regression analysis, showed that the value of the F test was 20,897. In this study the value of coefficient of determination showed 50.6, the model in this study were able to explain variation in the dependent variabel of 0.506 or 50.6%. The variables of Physical evidence/ tangible, Reliability/ Durability, Responsiveness, Assurance, Empathy, all have positive and significant of student satisfactionin service quality of Academic Administration part Faculty of Economics and Business Diponegoro University.